A standardisation of the Burt word reading test (Manawatu, 1976) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Eggers, Edwin McLean (Massey University, 1978)
The extent of the current uae of the Burt word Reading Test was investigated as a prelude to the production of normative data which would be valid for the Manawatu region. A review of the hiatory of the development and use of word resocngnition tests, and a review of the literature related to word recognition,were undertaken. Initially, schools In the area within, and adjacent to, palmerston North were canvassed In order to obtain Information regarding the extent to which the Burt Test remained in uae, and the purposes for which teachers administered the test. Strong support was obtained for the production of meaningful data in which teachers could have confidence, together with evidence that teachers still found the Burt to be a useful test. The co-operation of third year students at the palmerston north teachers' College was obtained, in administering the Burt to a large sample of pupils, and obtaining the other neoessary subject data. Results obtained support the view that the Burt Test remains a worthwhile instrument for use by teachers in the evaluation of reading behaviour. significant correlations were obtained between Burt scores and scores on the progressive Achievement Tests of Reading Conprehension and Vocabulary. Norms for pupils aged six to thirteen years were extracted and presented in ranges applicable to age groups, a new departurei in the presentation of data for the Burt test. Evidence was obtained that the order of the words on the burt (Rearranged) Word Reading Teat as produced by vernon (1938) is not appropriate for the testing of children in the Manawatu area of new Zealand, since there are marked cases of words being well out of difficulty order. It appears that although the Burt test samples only a limited aspect of reading behaviour, teachers may give some weight to the results they obtain as an indication of a child's level of reading progress. Other implications for teachers were considered as were implications for further research.
Keywords: Reading ability testing; Burt Word Reading Test; Manawatu; New Zealand